GAMBARAN TINGKAT PENGETAHUAN DAN SIKAP TENTANG KEKERASAN BERBASIS GENDER ONLINE PADA MAHASISWA PSIKOLOGI UNIVERSITAS UDAYANA - Janet, Noviana; Widyanthini, Desak Nyoman (ARCHIVE OF COMMUNITY HEALTH; Vol 12 No 1 (2025): April 2025, 2025)
ABSTRACT KBGO is a reproductive health problem that needs to be addressed in Indonesia, because it impacts psychological, social and work. OGBV’s treatment involves psychological analysis and assistance by professionals. Knowledge, attitudes, behavior, and beliefs influence the ability of psychologists to deal with cases of GBV. Therefore, research on the level of knowledge and attitudes of Psychology Students at the Faculty of Medicine, Udayana University is needed. This study used a descriptive cross-sectional design with a quantitative approach, the sampling technique for this study was consecutive sampling, and the data were obtained through a questionnaire.that was tested for the validity of the content and constructs of the MT-MM and the Cronbach Alpha reliability test. Data analysis techniques were carried out through descriptive analysis and cross-tabulation. The results of the study found 53.9% respondents had good knowledge about OGBV, even so OGBV knowledge of psychology students still needed to be improved, because there were still many students who answered incorrectly on the impact component. Meanwhile, 61.8% respondents had a disapproving attitude towards OGBV. Psychology Study Program of Udayana University expected can use the result of this research as reference material in developing strategies to increase knowledge and awareness of their student about Online Gender-Based Violence. Keywords: GBV, OGBV, Knowledge, Attitude